Análisis de un sistema integrado de adoquines permeables y drenaje sostenible para la gestión del agua lluvia urbana - Montalvo Méndez, Leonel Fernando (2025)
Rainwater is a resource whose management in urban environments has become a growing challenge due to soil impermeability and the limited capacity of conventional sewer systems. In this context, this research aimed to analyze the design of an integrated system of permeable paving stones and sustainable drainage to improve stormwater management in the city of Guayaquil. The methodology applied was experimental and descriptive. First, the main water accumulation problems in the study area were identified. Subsequently, permeable concrete prototypes with 9.5 mm aggregates were developed and subjected to laboratory compressive strength and infiltration tests. In addition, community information was collected through surveys to understand citizen perceptions of stormwater infrastructure. The results showed that the permeable concrete achieved sufficient strength for light traffic and, at the same time, exhibited a high infiltration capacity, with rates exceeding 22,800 mm/h, confirming its effectiveness in reducing runoff. The surveys revealed a critical assessment of the existing stormwater system, but also an openness to sustainable drainage alternatives. In conclusion, the study demonstrates that the integration of permeable paving stones and sustainable drainage is a viable and innovative alternative for Guayaquil. Its application would reduce flooding, optimize sewer system performance, and promote more resilient and environmentally responsible urban development.